Expanding approaches to teaching for diversity and social justice in K-12 education: Fostering global citizenship across the content areas - Tichnor-Wagner, Ariel; Parkhouse, Hillary; Glazier, Jocelyn; Cain, Jessie Montana (Education Policy Analysis Archives, 2016)
Educators today must be able to respond to the needs of an increasingly diverse student body and to teach all students the knowledge, skills, and attitudes needed for civic participation in a globalized, pluralist society. While state departments of education and national teacher organizations have begun to adopt global awareness in their teaching standards and evaluation tools, educators need to understand what globally competent teachers actually do in classrooms across subject areas and grade levels. This qualitative, multiple case study explores the signature pedagogies (Shulman, 2005) of 10 in-service teachers in one southeastern state who teach for global competence in math, music, science, English, social studies, and language classes across elementary, middle, and high schools. We found three signature pedagogies that characterized globally competent teaching practices across participants: 1) intentional integration of global topics and multiple perspectives into and across the standard curriculum; 2) ongoing authentic engagement with global issues; and 3) connecting teachers’ global experiences, students’ global experiences, and the curriculum. These signature pedagogies provide visions of possibility for concrete practices teachers can adapt to infuse global citizenship education into their own contexts and for policies that school districts and teacher education programs can consider in preparing and supporting teachers in this work.